1996
DOI: 10.1021/ma951116w
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Separation Processes and Self-Organization of Textures in the Biphase Region of Thermotropic Liquid Crystalline Poly(4,4‘-dioxy-2,2‘-dimethylazoxybenzene−dodecanedioyl). 2. A Study of the Isothermal Conditions

Abstract: The isothermal phase-separation process and the self-organization of textures in the biphase region of a thermotropic liquid crystalline polyester were investigated in situ by using polarizing light microscopy. When the test temperature was rapidly raised from room temperature to the temperature corresponding to the biphase region (T-jump) or rapidly lowered from a temperature corresponding to the isotropic phase to that corresponding to the biphase region (T-drop), the phase separation occurs as a consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…For thermotropic LCPs, the biphase structure that occurs during the anisotropic-isotropic transition may remain stable at thermal equilibrium over a certain temperature interval. This behavior has been observed for several nematic LCPs with chemically regular structures and was attributed to the polydispersity in the molecular mass [1][2][3][4][5][6][7][8][9][10]. For some of these polymers, it has been demonstrated that the chains are preferentially distributed in the isotropic and anisotropic phases of the biphasic region according to their length.…”
Section: Introductionmentioning
confidence: 86%
“…For thermotropic LCPs, the biphase structure that occurs during the anisotropic-isotropic transition may remain stable at thermal equilibrium over a certain temperature interval. This behavior has been observed for several nematic LCPs with chemically regular structures and was attributed to the polydispersity in the molecular mass [1][2][3][4][5][6][7][8][9][10]. For some of these polymers, it has been demonstrated that the chains are preferentially distributed in the isotropic and anisotropic phases of the biphasic region according to their length.…”
Section: Introductionmentioning
confidence: 86%
“…30 Moreover, TLCP clearing temperatures depend on molecular weight below a certain critical value. [30][31][32][33][34][35]51,52 Therefore, the temperature (T NI ) at which η goes through a maximum in Figure 10 corresponds to the clearing of the highest molecular weight fractions while the minimum (at a lower temperatures) corresponds to the clearing of the lowest molecular weight TLCP chains. If the polymer were monodisperse, the biphasic region in Figure 10 would be extremely narrow.…”
Section: Growth Of Shear Stress and Normal Stress Difference Upon Stamentioning
confidence: 98%
“…One prominent example arises in the phase separation of thermotropic nematic polymers, in which thermal processing leads to the formation and evolution of various biphasic morphologies involving nematic liquid crystalline and isotropic phases. The presence of internal orientational order, and anisotropic viscoelasticity of the liquid crystalline phase, is a source of additional driving forces in the evolution and coarsening of biphasic systems, as shown by Nakai et al …”
Section: Introductionmentioning
confidence: 97%
“…Liquid crystalline materials have been extensively investigated in the past decades 2,3 due to their numerous industrial applications that range, according to molecular weight and mesophase type, from electrooptics 4 to fiber manufacturing. , Due to the possibility of introducing surface-induced orientation, the interfacial properties of liquid crystals play a predominant role in electrooptical applications. , For example, physicochemical surface treatments exist which impart a specific molecular orientation at solid−liquid crystal interfaces . Recent developments in the design of multiphase composite materials by thermodynamic instabilities and in liquid crystalline polymer (LCP) fiber manufacturing pose new types of challenging problems involving the stability of liquid crystal fibers and networks and the dynamics of liquid crystalline surfaces. One prominent example arises in the phase separation of thermotropic nematic polymers, in which thermal processing leads to the formation and evolution of various biphasic morphologies involving nematic liquid crystalline and isotropic phases.…”
Section: Introductionmentioning
confidence: 99%